Gudali cattle of West and Central Africa - Tawah, C.L.; Rege, J.E.O. (Food and Agriculture Organization of the United Nations, 1996)
The objective of this paper was to compile the available information in the conventional and non-conventional literature on the origin, distribution, ecological settings, utility, husbandry practices and production systems of the Gudali, a West and Central African shorthorned zebu which is similar in conformation, size and origin to the East African shorthorned zebu. These animals are reputed not only for their beef and dairy qualities but also for their hardiness to the harsh northerly environments. Under the prevailing circumstances in the pastoral systems, natural selection is the primary force affecting any circumstances in the pastoral systems, natural selection is the primary force affecting any genetic change and, as a result, animals tend to perform relatively poorly. Most of the documented studies have been limited in scope and applicability. Therefore, further studies are needed to adequately characterize these animals under their different production systems.